Penguatan Pembelajaran Kimia Industri Melalui Dukungan Modul Ajar Berbasis Kebutuhan Industri di SMK Negeri 1 Air Putih - Pravil Mistryanto Tambunan; Aldella Makhfiza; Masdi Masdi; Rara Pramudhita; Yessi Febriani; Desi Natalia Siahaan; Syarifah Nadia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The misalignment between vocational education curricula and dynamic industrial requirements contributes significantly to graduate unemployment in the chemical manufacturing sector. This study evaluates a community engagement program designed to strengthen industrial chemistry instruction through the collaborative development and handover of industry integrated teaching modules at SMK Negeri 1 Air Putih in partnership with PT Bakrie Renewable Chemicals. Utilizing a non-empirical, participatory implementation framework, the intervention focused on upstream instructional enhancement without experimental sampling. The program generated a standardized annual teaching module encompassing effective lesson planning, industrial case studies, and safety protocols, thereby shifting instructional approaches toward case based and project based learning. Strategic institutional synergy established clear roles, placing pedagogical design under teacher ownership while the corporate partner provided technical context and document production support. A sustainable roadmap incorporating expert validation, periodic content updates, and digital media integration was established to maintain curriculum relevance. The findings demonstrate that upstream instructional support effectively bridges the school to work transition and reinforces vocational learning quality.